Warming springs and habitat alteration interact to impact timing of breeding and population dynamics in a migratory bird. (24th August 2018) - Kentie, Rosemarie; Coulson, Tim; Hooijmeijer, Jos C. E. W.; Howison, Ruth A.; Loonstra, A. H. Jelle; Verhoeven, Mo A.; Both, Christiaan; Piersma, Theunis
Abstract: In seasonal environments, increasing spring temperatures lead many taxa to advance the timing of reproduction. Species that do not may suffer lower fitness. We investigated why black‐tailed godwits ( Limosa limosa limosa ), a ground‐breeding agricultural grassland shorebird, have not advanced timing of reproduction during the last three decades in the face of climate change and human‐induced habitat degradation. We used data from an 11‐year field study to parameterize an Integral Projection Model to predict how spring temperature and habitat quality simultaneously influence the timing of reproduction and population dynamics. We found apparent selection for earlier laying, but not a correlation between the laying dates of parents and their offspring. Nevertheless, in warmer springs, laying dates of adults show a stronger positive correlation with laying date in previous springs than in cooler ones, and this leads us to predict a slight advance in the timing of reproduction if spring temperatures continue to increase. We also show that only in landscapes with low agricultural activity, the population can continue to act as a source. This study shows how climate change and declining habitat quality may enhance extinction risk. Abstract : Using long‐term field data of black‐tailed godwits, we modelled the combined effects of increasing spring temperature and declining habitat quality on laying dates and population dynamics. We examined how laying date affected fitness, and consequently population growth rates, and predicted how laying date would change over time. We found selection pressure for earlier laying, yet we predicted only a small advance in laying dates if spring temperatures continue to increase. We show that declining habitat quality amplifies negative effects of climate change: Only in the best‐quality habitats, we predicted no detrimental effects of spring warming on population growth rates.